Estimating carbon stocks of three traditional agroforestry systems and their relationships with tree diversity and stand density (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hartoyo APP, Khairunnisa S, Pamoengkas P, Solikhin A, Supriyanto, Siregar IZ, Prasetyo LB, Istomo. 2022. Estimating carbon stocks of three traditional agroforestry systems and their relationships with tree diversity and stand density. Biodiversitas 23: 6137-6146. One of the important sectors as a strategy for climate resilience and low carbon development in Indonesia is Forestry and Other Land Uses (FOLU) including the agroforestry sector. Carbon stock and tree diversity in an ecosystem are dynamic over time and still need to be investigated. This study was aimed: i) to estimate aboveground carbon stocks in the traditional agroforestry of Mount Halimun Salak National Park (MHSNP), in Kampung Birang and Kampung Merabu, East Kalimantan, as well as ii) to analyze the correlation between carbon stock with tree diversity and stand density in traditional agroforestry of Mount Halimun Salak National Park (MHSNP), in Kampung Birang and Kampung Merabu, East Kalimantan. The total plots were 75 plots (a plot size of 50x50 m), and carbon stock estimation was focused on pole and tree levels. The average carbon stock in the traditional zone of MHSNP, Kampung Birang, and Kampung Merabu respectively was 51.02 Mg C/ha, 96.25 Mg C/ha, and 82.17 Mg C/ha. The carbon stock in traditional agroforestry of all study sites was very significantly affected by the basal area (m2/ha) (p-val
Keywords: East Kalimantan, FOLU Net Sink, forest garden, Mount Halimun Salak National Park